Cellular Trafficking and Subcellular Interactions of Cationic Gene Delivery Nanomaterials - Barar, Jaleh; Omidi, Yadollah (Journal of Pharmacy and Nutrition Sciences, 2022)
Various cationic nanobiomaterials have been widely used as gene delivery nanosystems (GDNSs) in vitro and in vivo. Various cellular machineries are involved in trafficking of GDNSs, whose surface functional moieties and architectural properties confer great potential to interact with cell membranes and subcellular biomolecules. It appears such intrinsic inadvertent biological functionalities may impact the outcome of the biomedical applications of these nanobiomaterials. Various advanced materials used as GDNSs may display selective phenotypic effects in target cells/tissues as a result of initiation of various signaling pathways perhaps due to its cellular interactions with plasma cell membranes and/or intracellular compartments including genetic materials. Thus, better understanding about cellular/molecular impacts of GDNSs may maximize their clinical outcomes and accordingly minimize their inevitable undesired consequences. The main focus of this review is based on the cellular trafficking and interactions of cationic gene delivery nanobiomaterials with target cells or subcellular compartments.